ANALISIS PENILAIAN KINERJA PT. BANK BRI, TBK KANWIL MAKASSAR DENGAN PENDEKATAN BALANCE SCORECARD - A Muara Arumbarkah (BJRM (Bongaya Journal of Research in Management), 2019)
In certain periods, an assessment of a condition of the bank's financialstatements is needed to determine the organization's performance and its level of health.In this measurement contains information about the amount of assets (assets) owned aswell as liabilities and equity (own capital). Then it will also be illustrated the results of thebusiness obtained by the bank as well as the expenses and costs incurred to obtain theseresults in a certain period. This study aims to analyze the performance of PT. Bank BRI,Tbk using the balanced scorecard approach which is reflected through four mainperspectives, namely financial perspective, customer perspective, internal businessperspective and growth and learning perspective. This study uses a case study approachsupported by a survey that collects information about factors related to the researchvariable. With the Balance Score-card approach. Expected measurement model. Thisanalytical method can provide accurate and detailed answers. The results of this studyindicate that Financial Perspective (X3) is the most dominant variable influencing BRIBank Performance (Y) The relationship between variables X and Y is very strong indicatingthat the variable Financial Perspective, Customer Perspective, Internal BusinessPerspective & Growth and Learning Perspective have influence a very significant (96.4%)effect on BRI Bank Performance (Y) while theoretical conclusions are all variables thathave a significant effect.